The role of emotions and perceived control in the recovery strategy of service companies - Kolos, Krisztina; Kenesei, Zsófia (Applied Studies in Agribusiness and Commerce, 2009)
The purpose of this study is to investigate the effectiveness of service recovery tactics. The reseach included a qualitative study based on 30 interviews with customers and employees of a telecommunication company. This was followed by a quantitative study using between subject experimental designs based on scenarios. Our research results suggest that employees’ positive emotions and perceived control during the recovery process make consumers more satisfied.